PERANCANGAN SISTEM INFORMASI E-LEARNING PADA SMA NEGERI 5 BUKITTINGGI MENGGUNAKAN BAHASA PEMPROGRAMAN PHP DAN DATABASE MYSQL - Hardiyanti Putri, Stefani (CV Nature Creative Innovation, 2024)
Utilization of computers in society is growing. One result of advances in information technology is the manufacture of E-LEARNING used as a medium of learning, the collection task, download material and conduct a question and answer between teachers and students. Implementation of e-learning in SMA NEGERI 5 BUKITTINGGI is in need because if there are no entry barriers like teachers teach and the material can not be conveyed. With e-learning students can access material that is fed by the teacher during lessons in the classroom do not take place. If the student does not attend school while learning face to face in the classroom, students can collect a task, download the material, and conduct a question and answer with the teacher of the subject matter by utilizing e-learning.